Perencanaan dalam Administrasi Pendidikan - Adha Zam Zam Hariro; Nabila Ulkhaira; Rizki Ramadhani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Planning in educational administration is a key element in achieving educational goals effectively and efficiently. This article discusses various aspects of planning in the context of educational administration, as educational planning has several characteristics such as continuous intellectual development, problems, needs, situations, formulating policies and outlining educational strategies and so on. Meanwhile, the principles include interdisciplinary, objective, flexible, comprehensive and others. Educational planning has several types, including macro, meso and micro planning. Apart from that, there are also short-term and long-term planning. Educational planning is very important and useful as a guide, direction, concept in achieving a goal. Through literature reviews and case studies, this article explores planning strategies and methods used by educational institutions to improve the quality of education. The research results show that systematic and structured planning can improve school performance, increase staff involvement, and improve student learning outcomes.